Decreased Openness to Experience Is Associated with Migraine-Type Headaches in Subjects with Lifetime Depression - Magyar, Mate; Gonda, Xenia; Pap, Dorottya; Edes, Andrea; Galambos, Attila; Baksa, Daniel; Kocsel, Natalia; Szabo, Edina; Bagdy, Gyorgy; Elliott, Rebecca; Kokonyei, Gyongyi; Juhasz, Gabriella (Frontiers in Neurology, 2017)
Introduction: Migraine and depression frequently occur as comorbid conditions, and it has been hypothesised that migraine with and without depression may have a different genetic background. A distinct personality trait constellation has been described in migraineurs. Less attention, however, was paid to personality differences in migraineurs with and without depression which may also shed light on differences in the neurobiological background. The aim of our study was to investigate big five personality traits, headaches and lifetime depression in a large European general population sample. Methods: Relationship between lifetime depression, Big Five Inventory personality traits and headaches identified by the ID-Migraine Questionnaire were investigated in 3026 individuals from Budapest and Manchester with multivariate and logistic regression analyses. Results: Both lifetime depression and migraine(ID) showed differences in personality traits. Neuroticism was an independent risk factor for both conditions while a significant interaction effect appeared between the two in the case of openness. Namely, subjects with migraine(ID) and without lifetime depression scored higher on openness compared to those who had depression. Conclusion: While we confirmed previous results that high neuroticism is a risk factor for both depression and migraine, openness to experience was significantly lower in the co-occurrence of migraine and depression. Our results suggest that increased openness, possibly manifested in optimal or advantageous cognitive processing of pain experience in migraine may decrease the risk of co-occurrence of depression and migraine and thus may provide valuable insight for newer prevention and intervention approaches in the treatment of these conditions.